Pengaruh Brand Image dan Promotion Terhadap Customer Loyalty pada Pengguna Brand Kecantikan Wardah - Putri Nurmalasari; Rafi’ah Kumalasari; Gina Aulia Dewi; Mawar Ayu Lestari; Retno Purwani Setyaningrum (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of Brand Image and Promotion on Customer Loyalty for Wardah beauty brand users in Indonesia. The increasingly competitive beauty industry requires companies to maintain customer loyalty through a strong brand image and effective promotional strategies. The research method used is associative quantitative with data collection techniques through questionnaires to 55 respondents. Data analysis techniques include validity, reliability, multiple linear regression, t test, F test, and coefficient of determination using SPSS 24. The results showed that Brand Image and Promotion had a partial and simultaneous effect on Customer Loyalty. The coefficient of determination (R²) value of 0.539 indicates that 53.9% of the variation in customer loyalty can be explained by the two independent variables. The t test shows that Brand Image (t = 2.983; p < 0.05) and Promotion (t = 3.918; p < 0.05) have a significant effect partially, while the F test shows a significant simultaneous effect (F = 30.420; p < 0.001). These findings confirm the importance of synergy between brand image and promotion in building customer loyalty, especially in the face of increasingly dynamic cosmetic market competition.